2021
DOI: 10.24115/s2446-6220202173d1751p.609-622
|View full text |Cite
|
Sign up to set email alerts
|

Translation strategies for tourist advertising sites

Abstract: This article is devoted to the study of modern strategies for translating tourist-oriented Internet texts. Misuse or omission of expressive means in translated texts may lead to distortion of information and loss of the reader’s interest. Therefore, the aim of the research is to study translation methods and strategies making quality translation of tourist texts possible. The research material comprised tourist texts presented on English-language tourist sites. The following methods were used to reach the obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Surely, it is an attempt of Russians not only to wipe out Ukrainian culture, but also Ukrainian identity. In the analysis of translation strategies, Tukhtabayeva et al (2021) reported that translation of proper names should begin with the search for ready-made matches; if there are no such matches, the translator should translate them at the morpheme level using such transformations as transliteration or transcription. When it comes to historical and architectural monuments in Ukraїner, proper names are rendered for the target Englishspeaking audience by means of combination of an existing equivalent and transcoding.…”
Section: Diagnostic Methods For Assessing the Readiness Of Future Mar...mentioning
confidence: 99%
“…Surely, it is an attempt of Russians not only to wipe out Ukrainian culture, but also Ukrainian identity. In the analysis of translation strategies, Tukhtabayeva et al (2021) reported that translation of proper names should begin with the search for ready-made matches; if there are no such matches, the translator should translate them at the morpheme level using such transformations as transliteration or transcription. When it comes to historical and architectural monuments in Ukraїner, proper names are rendered for the target Englishspeaking audience by means of combination of an existing equivalent and transcoding.…”
Section: Diagnostic Methods For Assessing the Readiness Of Future Mar...mentioning
confidence: 99%